2009
DOI: 10.1590/s1517-70762009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização mecânica das argamassas de assentamento para alvenaria estrutural - previsão e modo de ruptura

Abstract: RESUMOEste trabalho pretende avaliar o comportamento mecânico das argamassas de assentamento para o uso estrutural, por meio das propriedades de resistência à compressão, tração na flexão e módulo de elasticidade, sob estados de tensões uniaxial e multiaxial. Portanto, estabelecer correlações entre os resultados mecânicos de diferentes traços de argamassas, relações água/cimento e geometria da amostra associada ao modo de ruptura. As principais conclusões obtidas, entre outras, são: existe uma relação potencia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
2
4
0
1
Order By: Relevance
“…A clear trend for the compressive strength decreases as the w/c ratio increases was found for all mortar mixes. This result is in agreement to results pointed out by (Appa Rao [13]; Mohamad et al [20]; Fernandes et al [33]). The increase in the w/c ratio means that there is more water between the solid particles and consequently there are more voids in hardened condition, increasing porosity and consequently leading to the decrease on the compressive strength.…”
Section: Compressive Strengthsupporting
confidence: 93%
See 2 more Smart Citations
“…A clear trend for the compressive strength decreases as the w/c ratio increases was found for all mortar mixes. This result is in agreement to results pointed out by (Appa Rao [13]; Mohamad et al [20]; Fernandes et al [33]). The increase in the w/c ratio means that there is more water between the solid particles and consequently there are more voids in hardened condition, increasing porosity and consequently leading to the decrease on the compressive strength.…”
Section: Compressive Strengthsupporting
confidence: 93%
“…Differences in the compressive strength due to the shape of specimens occur basically due to the slenderness of the samples (height to length ratio) and to the boundary restraint between the loading platens and the specimen. The experimental results of this study clearly indicated a difference between cylindrical (f c ) and prismatic (f p ) compressive strength of mortars, as observed also by Mohamad et al [20]. Prismatic specimens exhibited a higher compressive strength, which is agreement with the conclusions of Del Viso et al [30] and Stahli and Van Mier (2007), who observed that large specimens exhibit lower values of resistance than small specimens.…”
Section: Compressive Strengthsupporting
confidence: 91%
See 1 more Smart Citation
“…Masonry strength depends not only on bricks and mortar strength, but also on factors such as joints thickness (Monteagudo et al, 2015), irregularities in the surfaces, water absorption (Rozo Rincón et al, 2014), maximum mortar aggregate size (Salamanca, 2001), size and pattern of the brick perforations, mortar shrinkage (Mohamad et al, 2009), quality of the workforce, brickwork, and so on (Arredondo, 1956).…”
Section: Compressive Strength Of Brickwork Specimensmentioning
confidence: 99%
“…O tipo de ruptura observado foi o mesmo observado por MOHAMAD [15] e [16] para prismas assentados com argamassa de traço 1:1:6 (proporção em volume entre cimento: cal: areia), ruptura dúctil com esmagamento da junta de assentamento e, para prismas assentados com argamassas de traço 1:1/4:3, ruptura frágil com trincas verticais cortando o bloco e argamassa. Os autores verificaram que as diferenças de deformação específica entre o bloco e a argamassa ocasionaram um aumento nas tensões de tração do bloco e, com isso, uma ruptura da alvenaria com cargas menores.…”
Section: Resistência Da Argamassaunclassified